2010
DOI: 10.1159/000312130
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Are Required for the Induction of Bronchial Hyperresponsiveness in a Th Transfer Model of BALB/c Background

Abstract: Background: Helper T (Th) cells are deeply involved in the pathophysiology of bronchial asthma, such as eosinophilic inflammation, bronchial hyperresponsiveness (BHR), airflow limitation and remodeling. It is still unclear whether Th cells contribute to BHR independently of eosinophilic inflammation. The double GATA (dblGATA) site is a high-affinity GATA-binding site in the GATA-1 promoter. dblGATA site-deficient (ΔdblGATA) mice lack eosinophils. Method: Ovalbumin (OVA)-reactive Th clones were transferred into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…And airway hyperresponsiveness is a well-established consequence of eosinophil infiltration (Kay, 2005; Watt et al, 2005; Kanda et al, 2009; Kim and Lee, 2009; Walsh, 2010). There is evidence that eosinophils are involved in the bronchial hyperresponsiveness mediated by T-cell (Ohtomo et al, 2010). Iwashita et al (2006) showed in a murine model of airway hyperresponsiveness that eosinophil chemotactic factor by T lymphocytes (ECF-L) expression was observed soon after allergen exposure but before the onset of airway inflammation, indicating that ECF-L is a selectively expressed protein in the airway hyperresponsiveness and may play a critical role in allergic inflammation.…”
Section: Airway Hyperresponsivenessmentioning
confidence: 99%
“…And airway hyperresponsiveness is a well-established consequence of eosinophil infiltration (Kay, 2005; Watt et al, 2005; Kanda et al, 2009; Kim and Lee, 2009; Walsh, 2010). There is evidence that eosinophils are involved in the bronchial hyperresponsiveness mediated by T-cell (Ohtomo et al, 2010). Iwashita et al (2006) showed in a murine model of airway hyperresponsiveness that eosinophil chemotactic factor by T lymphocytes (ECF-L) expression was observed soon after allergen exposure but before the onset of airway inflammation, indicating that ECF-L is a selectively expressed protein in the airway hyperresponsiveness and may play a critical role in allergic inflammation.…”
Section: Airway Hyperresponsivenessmentioning
confidence: 99%
“…To further analyze mechanisms of LAR, we developed a T-cell-dependent asthma model in which T helper (Th) clones were adoptively transferred into unprimed mice [9]. In addition to eosinophilic inflammation, airway hyperresponsiveness and remodeling [10,11], bronchoconstriction was induced in this model [11,12]. An ovalbumin (OVA)-reactive Th clone, T6-2, conferred LAR, while another Th clone, BF7, induced airway hyperresponsiveness upon OVA challenge [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to eosinophilic inflammation, airway hyperresponsiveness and remodeling [10,11], bronchoconstriction was induced in this model [11,12]. An ovalbumin (OVA)-reactive Th clone, T6-2, conferred LAR, while another Th clone, BF7, induced airway hyperresponsiveness upon OVA challenge [12]. These distinctive asthmatic reactions stemmed from the characteristics of transferred Th clones, but humoral immune response was not involved.…”
Section: Introductionmentioning
confidence: 99%
“…Besides an eosinophilic inflammation, bronchoconstriction was induced in this model [13]. An ovalbumin (OVA)-reactive Th clone, T6–2, conferred LAR, while another Th clone, BF7, induced airway hyperresponsiveness upon OVA challenge [13,14]. These distinctive asthmatic reactions resulted from the characteristics of transferred Th clones, while humoral immune reactions were not involved.…”
Section: Introductionmentioning
confidence: 99%